PENGARUH CORPORATE SOCIAL RESPONSIBILITY , UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP EARNINGS RESPONSE COEFFICIENTS Studi Empiris pada Bank Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2010-2019. - Ita Kusumawati; Muhammad Zilal Hamzah; Agustina Suparyati; Swanto Sirait (Jurnal Penelitian Akuntansi (JPA), 2021)
This research aimed to examine the effect of Corporate Social Responsibility (CSR), Firm Size, Capital Structure, and Profitability to Earnings Response Coefficient (ERC). This matter caused by Corporate Social Responsibility (CSR) become responsibility to company in improving care for environment and social. It certainly can change the financial structure in some company and it may change the way of thinking the investor will react to this matter. In this study the number of samples used in this study were 15 companies in the period 2010 to 2019. The method used is the panel data regression method by E-views 10 program. The analysis result show that together Corporate Social Responsibility (CSR), Firms Size, Capital Structure, and Profitability simultaneously affect the Earnings Response Coefficient (ERC). Partial test show that Corporate Social Responsibility (CSR), Size, Capital Structure, and Profitability affect the Earnings Response Coefficient (ERC).